Timing analysis of the black hole candidate EXO 1846–031 with Insight-HXMT monitoring - Liu, He-Xin; Huang, Yue; Xiao, Guang-Cheng; Bu, Qing-Cui; Qu, Jin-Lu; Zhang, Shu; Zhang, Shuang-Nan; Jia, Shu-Mei; Lu, Fang-Jun; Ma, Xiang; Tao, Lian; Zhang, Wei; et al. (Research in astronomy and astrophysics, 2021)
We present the observational results from a detailed timing analysis of the black hole candidate EXO 1846–031 during its outburst in 2019 with the observations of Insight -HXMT, NICER and MAXI . This outburst can be classified roughly into four different states. Type-C quasi-periodic oscillations (QPOs) observed by NICER (about 0.1–6 Hz) and Insight -HXMT (about 0.7–8 Hz) are also reported in this work. Meanwhile, we study various physical quantities related to QPO frequency. The QPO rms–frequency relationship in the energy band 1–10 keV indicates that there is a turning pointing in frequency around 2 Hz, which is similar to that of GRS 1915+105. A possible hypothesis for the relationship above may be related to the inclination of the source, which may require a high inclination to explain it. The relationships between QPO frequency and QPO rms, hardness, total fractional rms and count rate have also been found in other transient sources, which can indicate that the origin of type–C QPOs is non-thermal.